2017
DOI: 10.1007/s00701-017-3184-2
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for surgical site infections among 1,772 patients operated on for lumbar disc herniation: a multicentre observational registry-based study

Abstract: In summary, this study clearly lends support to the use of PAT in surgery for lumbar disc herniation. Senior surgeons assisting inexperienced colleagues to avoid prolonged duration of surgery could also reduce the occurrence of SSI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…Six studies investigated the relationship between obesity and postoperative SSI. 30 32 , 35 , 36 , 43 The pooled result showed that obesity patients had a 2.87-fold increased risk of SSI than those of normal weight (RR 2.87, 95% CI 1.62–5.09; P <0.001). This indicated that obesity was a significant risk for SSI.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…Six studies investigated the relationship between obesity and postoperative SSI. 30 32 , 35 , 36 , 43 The pooled result showed that obesity patients had a 2.87-fold increased risk of SSI than those of normal weight (RR 2.87, 95% CI 1.62–5.09; P <0.001). This indicated that obesity was a significant risk for SSI.…”
Section: Resultsmentioning
confidence: 98%
“…Nine studies investigated the relationship between current smoking and postoperative SSI. 28 , 30 32 , 34 , 35 , 37 , 39 , 43 Pooled estimates showed that current smokers had a comparable rate of postoperative SSI than nonsmokers (RR 0.89, 95% CI 0.75–1.06; P =0.178; Figure 5 ). This indicated that current smoking did not increase the risk of postoperative SSI in patients with lumbar spine surgery.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Predictors of infection following microdiscectomy include absence of prophylactic antibiotic dosing and duration of surgery > 68 min [90]. Interestingly, one study did not find that preoperative lumbar epidural CSI increased infection risk [91].…”
Section: Open Discectomymentioning
confidence: 99%